2013
DOI: 10.4162/nrp.2013.7.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Lotus leaf alleviates hyperglycemia and dyslipidemia in animal model of diabetes mellitus

Abstract: The purpose of this study was to investigate the effects of lotus leaf on hyperglycemia and dyslipidemia in animal model of diabetes. Inhibitory activity of ethanol extract of lotus leaf against yeast α-glucosidase was measured in vitro. The effect of lotus leaf on the postprandial increase in blood glucose levels was assessed in streptozotocin-induced diabetic rats. A starch solution (1 g/kg) with and without lotus leaf extract (500 mg/kg) was administered to the rats after an overnight fast, and postprandial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Lotus extract has been reported to have an effect of reducing fasting blood glucose, total cholesterol, and triglyceride in diabetic animals, thus showing anti-diabetic and antilipid effects [ 15 ]. In addition, it has been reported that lotus extract has an effect of improving obesity and hyperlipidemia [ 16 ], reducing blood glucose [ 17 ], anti-oxidation, and protecting neurons [ 18 ] in animals with high fat diet-induced obesity. Also, it has been known that long-term use of lotus leaves might exert a suppressive effect on adipose tissue differentiation at the cellular level [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lotus extract has been reported to have an effect of reducing fasting blood glucose, total cholesterol, and triglyceride in diabetic animals, thus showing anti-diabetic and antilipid effects [ 15 ]. In addition, it has been reported that lotus extract has an effect of improving obesity and hyperlipidemia [ 16 ], reducing blood glucose [ 17 ], anti-oxidation, and protecting neurons [ 18 ] in animals with high fat diet-induced obesity. Also, it has been known that long-term use of lotus leaves might exert a suppressive effect on adipose tissue differentiation at the cellular level [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The earlier studies showed that the serum lipid level decreased significantly in high-fat rabbit diet by providing rabbit with Crataegus pinnatifida which is rich in total flavonoids from Crataegus pinnatifida, meanwhile, it has been confirmed that Astragalus membranaceus and Codonopsis pilosula could protect the liver and the heart, which also benefits for lipid metabolism (Jiang et al, 2013;Li et al, 2012;Wu et al, 2014). Moreover, some reports showed that Lotus leaf leads to a decrease in the levels of serum lipid (Cho et al, 2007;Kim et al, 2013). Furthermore, many studies uncovered that TCM could affect total lipid metabolism by reducing serum lipid level (Guo et al, 2015;Kwon et al, 2005;Tu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…, anticancer (Nakamura et al, 2013), hypolipidemic, weight loss (Wu et al, 2010), antibacterial and anti-inflammatory (Liu et al, 2013) effects and can prevent cardiovascular diseases (Subashini & Rajadurai, 2011) and diabetes (Kim et al, 2013).…”
Section: Jementioning
confidence: 99%
“…It also has numerous food and medicinal applications (Huang et al, ; Lin, Kuo, Lin, & Chiang, ). Modern medical research has shown that lotus leaf possesses anti‐HIV (Yoshiki et al, ), antioxidant (Lee, Kim, & Je, ), anticancer (Nakamura et al, ), hypolipidemic, weight loss (Wu et al, ), antibacterial and anti‐inflammatory (Liu et al, ) effects and can prevent cardiovascular diseases (Subashini & Rajadurai, ) and diabetes (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%